2020
DOI: 10.3390/cells9010129
|View full text |Cite
|
Sign up to set email alerts
|

Mutations That Confer Drug-Resistance, Oncogenicity and Intrinsic Activity on the ERK MAP Kinases—Current State of the Art

Abstract: Unique characteristics distinguish extracellular signal-regulated kinases (Erks) from other eukaryotic protein kinases (ePKs). Unlike most ePKs, Erks do not autoactivate and they manifest no basal activity; they become catalysts only when dually phosphorylated on neighboring Thr and Tyr residues and they possess unique structural motifs. Erks function as the sole targets of the receptor tyrosine kinases (RTKs)-Ras-Raf-MEK signaling cascade, which controls numerous physiological processes and is mutated in most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 113 publications
0
34
0
Order By: Relevance
“…They are also involved in actin polymerization via their interaction with different actin regulatory proteins [ 16 ]. Additionally, ERK1/2 are implicated in the development of multiple types of cancers (reviewed in [ 17 , 18 ]). Consistent with their critical roles in tumorigenesis, targeting these enzymes present nowadays an outstanding interest for different therapeutic purposes [ 18 ].…”
Section: The Conventional Mapksmentioning
confidence: 99%
“…They are also involved in actin polymerization via their interaction with different actin regulatory proteins [ 16 ]. Additionally, ERK1/2 are implicated in the development of multiple types of cancers (reviewed in [ 17 , 18 ]). Consistent with their critical roles in tumorigenesis, targeting these enzymes present nowadays an outstanding interest for different therapeutic purposes [ 18 ].…”
Section: The Conventional Mapksmentioning
confidence: 99%
“…The MAPK/ERK pathway is one of the major targets of anti-tumor therapies in several malignancies as gain-of-function mutations of this pathway are collectively associated with more than 90% of cancers ( Nissan et al, 2013 ; Smorodinsky-Atias et al, 2020 ). The cascade involves the sequential activation of receptor tyrosine kinases (RTK), RAS GTPases, RAF kinases (MAP3K), MEK (MAP2K), which ultimately phosphorylates ERK (MAPK) ( Lee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic targeting of ERK is of key interest since ERK inhibitors (ERKi) have the potential to overcome common drug resistance to “upstream” MEK/RAF/RAS inhibitors ( Ryan and Corcoran, 2018 ; Smorodinsky-Atias et al, 2020 ). Indeed, ERKi therapies are expected to show greater antitumor efficacy in advanced metastatic and multidrug-resistant tumors with reactivated MAPK signaling, however, their broad clinical use is limited ( Lee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ERK remains inactive until two amino residues within the activation loop are phosphorylated by mitogen-activated kinase (MEK) in response to extracellular growth factors. The ERK signaling pathway is involved in regulating cell proliferation, differentiation, and survival (Chaikuad et al, 2014;Goetz et al, 2014;Tong and Seeliger, 2015;Jaiswal et al, 2018;Pegram et al, 2019;Smorodinsky-Atias et al, 2020). It has been found that the tumor is resistant to ERK inhibitor treatment when the patient is continuously administered a small molecule inhibitor.…”
Section: Introductionmentioning
confidence: 99%